UTILIZING THE VISUAL SIMULATION MEDIA TO REDUCE STUDENTS' MISCONCEPTIONS ON ASTRONOMIC MATERIALS IN HIGH SCHOOL GEOGRAPHY LESSONS - Puji Lestari, Meryani
This research was motivated by the number of students' mistakes in understanding the basic knowledge of astronomy in high school’s Geography subjects, especifically those related to the topic of the Earth - Moon and Sun system. The aim of the study is to identify students' misconceptions and to study how effective the utilization of visual simulation media may reduce these misconceptions. This research is an experimental study with a pre-experimental method. The research design is one group pre-test – post-test. The population of this study is 211 10th grade students of SMAN 1 Pangkalpinang in the academic year 2020- 2021. The data collecting was conducted by using a four-tier multiple choice diagnostic test (multiple four-tier test) in combination with CRI (Certainty Responses of Index) method to measure the students’ understanding and identify misconceptions. The learning media used were digital and non-digital-based visual simulation media. The study showed that: (1) students’ misconceptions are identified mostly on the topics of Coriolis effect, daily apparent motion of the Sun, annual apparent motion of the Sun, difference between the length of day and night, intensity of solar radiation, and eclipses; (2) students’ understanding on the topic of impacts of Earth's rotation and revolution increased after being given learning experience utilizing visual simulation media, while the percentage of students showing misconceptions decreased; (3) after the treatment that utilized visual simulation, the average student individual misconceptions reduced by 76.32% (high category), and the average misconceptions towards each problem being tested decreased by 96.91% (high category). Thus, it can be concluded that the utilization of visual simulation media is very effective in reducing misconceptions that 10th grade studentsat SMAN 1 Pangkalpinang have towards the concept of the impacts of Earth's rotation and revolution.